Atividade docente e inclusão : as medições da consultoria colaborativa - Dounis, Alessandra Bonorandi (2013)
This study aimed to analyze the activity of a teacher involved in a process of Collaborative Consulting to school inclusion of a student with cerebral palsy. To achieve it, we opted for developing a qualitative research with approach Socio- Historical (FREITAS, 2002; 2007; 2010), anchored in epistemological assumptions of Vygotsky (1988; 1996; 1997; 2004; 2010) and the Clinic Activity Clot Yves (2007; 2010). We carry out a process of Collaborative Consulting in the period May to December 2011, with a teacher of first year of elementary school public of the city of Maceió, he had in his classroom a student with cerebral palsy. This process of Collaborative Consulting was based on prescription and manufacture of assistive technology resources to areas of Augmentative and Alternative Communication, mobility and pedagogical adaptation, in order to promote learning and participation this student in the activities proposed by the teacher. For data collection, we used the procedures of reflexive interview, collaborative observation , the video recording and selfconfrontation simple. The empirical result of the data collection was analyzed by thematic analysis, which demanded the construction of three themes, namely: Inclusion: building possibilities for a real activity; Training and working conditions - the inclusion happens in half and Inclusion: the challenge to professional development. From the analysis of these categories, we observed that the significations made by the teacher about their teaching and the inclusion are mediated by culture, by his life story and the material conditions offered by the school and by the public power. Identified yet that the teacher is mediated by their professional gender but has a marked style, with the use of a subjective catachresis, in which identifies the difficulties of his profession as challenges to be overcome and that contribute to their professional development. Additionally, we also note that the processes of Collaborative Consulting and Selfconfrontation Simple acted on the zone of proximal development of the teacher, confirming the possibility of using both procedures like strategies of training teachers for inclusive education.